Eksistensi Penganut Agama Parmalim Dalam Negara Demokrasi Indonesia - Mangido Nainggolan (Mahesa Research Center, 2021)
Every belief system are strongly influenced by culture, owned by adherents of that belief. North Sumatra is one of the areas in Indonesia who uphold the values of democracy which has been formulated in Pancasila and the 1945 Constitution. Parmalim religion group is a movement of spiritual exercises that move to defend and uphold the values and custom of the ancient belief are endangered. This spiritual movemen develoved in batak lands at once became a political movement that unifies batak to oppose the Netherlands 1883 or seven year before death Sisingamangaraja XII. Its diversity of tribes and religions in Indonesia should be made into a pride and wealth of is priceless because it is part of the identity of the nation itself. The diversity of it would be so wonderful if it cansoexist with mutual respect, appreciate and uphold the values of unity, mutual respect and mutual building to manifest prosperity together, the presence of adherents tend to beabused and Parmalim marginalized should be eliminated as the embodiment and the recognition of Human Right as well as the preservation of the values of Pancasila in accordance with the constitution..